2004
DOI: 10.1037/0735-7044.118.3.563
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Amnesia Induced by Drugs Acting on Different Molecular Systems.

Abstract: The gamma aminobutyric acid-A (GABA-sub(A)) agonist, muscimol, the glutamate N-methyl-D-aspartate (NMDA) receptor antagonist, D-2-amino-5-phosphonopentanoic acid (AP5), and the inhibitor of the extracellularly regulated kinases (ERKs), UO 126, cause retrograde amnesia when administered to the hippocampus. In the present study, the authors found that they all cause retrograde amnesia for 1-trial inhibitory avoidance, not only when infused into the dorsal CA1 region of the hippocampus, but also when infused into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 39 publications
7
64
1
Order By: Relevance
“…Here, we reported that aripiprazole caused significant changes in STM and LTM in the inhibitory avoidance task, with an improvement in the performance of the animals (longer latency to climb down the platform) when compared to the control group. The inhibitory avoidance task has been used to hypothesize that several biochemical mechanisms may influence memory [22,23] . This task is heavily dependent on the hippocampus, where a sequence of molecular events takes place.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we reported that aripiprazole caused significant changes in STM and LTM in the inhibitory avoidance task, with an improvement in the performance of the animals (longer latency to climb down the platform) when compared to the control group. The inhibitory avoidance task has been used to hypothesize that several biochemical mechanisms may influence memory [22,23] . This task is heavily dependent on the hippocampus, where a sequence of molecular events takes place.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that SSR180711 reversed the deleterious effects of MK-801 in the object recognition task when the psychotomimetic was administered in the immediate post-acquisition interval, thus affecting consolidation and/or recall processes. It can be speculated that the effects of SSR180711 are mediated via a7 n-AChRs that indirectly mediate glutamate release in the hippocampus and the amygdala, two structures well known to be important for information processing in the post-training period (Rossato et al, 2004). It is important to note that the positive effects of SSR180711 in the object recognition test in mice using a long-term forgetting delay are mediated by the a7 n-AchR, as they were abolished by the genetic deletion of this receptor subtype.…”
Section: Profile Of Ssr180711 In Tests Predictive Of Therapeutic Actimentioning
confidence: 99%
“…The test session step-down latency depends on the intensity of the footshock. Using 0.4-0.5 mA, 2-sec footshock, test step-down latency is usually of about 40 sec; if the training footshock is higher (0.8-1.0 mA the retention score is usually much higher (3 or more min) (Quevedo et al 2005, Cammarota et al 2004, 2005. Inhibition of their natural exploratory tendency to explore beyond the safe area constitutes a conditioned avoidance response; i.e., an instrumental conditioned reflex.…”
Section: Inhibitory Avoidance Learning: Learning Little and Learning mentioning
confidence: 99%
“…Infusion volume was 0.5 μl/side. Infusions lasted 30 sec on each side, and the cannulae were kept in place for an additional 15 sec (Izquierdo et al 1992, Izquierdo and Medina 1997, Cammarota et al 2004, 2005. Some of the treatments were given at the times mentioned before or after a single training session (Tr1) and these animals were tested just once (T1).…”
Section: Inhibitory Avoidance Learning: Learning Little and Learning mentioning
confidence: 99%
See 1 more Smart Citation